Application of the averaging method to some optimal control problems - Mogileva, Victoria; Stanzhytskyi, O.; Tkachuk, Alla (My University, 2013)
An optimal control problem for non-linear differential equations system with small parameter has been considered. To the study of such problems the application of the averaging method is justified.
Keywords: оптимальне керування; малий параметр; метод усереднення; інфімум; optimal control; small parameter; averaging method; infimum; кафедра вищої математики імені проф. Можара В. І.